PENINGKATAN KEAKTIFAN DAN TANGGUNG JAWAB BELAJAR MAHASISWAMELALUI PENGGUNAAN MODELCOOPERATIVE LEARNING TIPE TWO STAY TWO STRAY PADA KEGIATAN LESSON STUDY MATA KULIAH PERKEMBANGAN PESERTA DIDIK - Aprilia, Nani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The development of Student is one of lectures in the department of Biology Education, Faculty of Teacher Training and Education, Ahmad Dahlan University; in the second semester. The common learning strategy, expository strategy, was useless in increasing the activeness and learning responsibility of students. One of efforts to overcome the problem was a Lesson Study. The lesson Study implements models, strategies, approaches, and methods which is appropriate to situation, conditions and problems faced in learning activities. Lesson Study was carried out by a number of lectures in three scientific activities, planning (Plan), implementation (do) and reflection (see).The aim of this research was to implement Cooperative Two Stay Two Stray learning model in order to improve the activeness and responsibility of students during the implementation of lesson study. The lesson study was carried out by involving 4 lectures and 50 students. Data of activeness and responsibility were collected and then further analyzed. The result shows that the implementation of Cooperative Two Stay Two Stray learning model during the implementation of lesson study increased the activeness and learning responsibility of students.Â Keywords :activeness , learning responsibility , cooperative learning model - Stay Two Two stray